Evaluasi Efektivitas Intervensi Keperawatan Komunitas dalam Mengatasi Masalah Kesehatan Masyarakat di Wilayah Desa Bunde, Kabupaten Mamuju, Sulawesi Barat Tahun 2024 - Musdalifah, Musdalifah (Barongko: Jurnal Ilmu Kesehatan, 2025)
Community nursing interventions are a strategic approach to improving public health through promotive, preventive, curative, and rehabilitative programs. This study aims to evaluate the effectiveness of community nursing interventions in addressing public health problems in Bunde Village, Mamuju Regency, West Sulawesi, in 2024. The research method used a quantitative descriptive approach with a cross-sectional design. Respondents, 120 heads of families, were selected using proportional random sampling. Data were collected through questionnaires and in-depth interviews, then analyzed using frequency distribution and chi-square tests. The results showed that community nursing interventions were effective in increasing access to health services (78%), community knowledge about health (74%), and clean and healthy living behaviors (71%). The most influential factors were support from health cadres and the active role of community nurses. This study concluded that community nursing interventions contributed significantly to reducing public health problems. It is recommended that cross-sector collaboration and training of local cadres be increased to strengthen the program's sustainability.